2021
DOI: 10.7554/elife.56645
|View full text |Cite
|
Sign up to set email alerts
|

Corticothalamic gating of population auditory thalamocortical transmission in mouse

Abstract: The mechanisms that govern thalamocortical transmission are poorly understood. Recent data have shown that sensory stimuli elicit activity in ensembles of cortical neurons that recapitulate stereotyped spontaneous activity patterns. Here, we elucidate a possible mechanism by which gating of patterned population cortical activity occurs. In this study, sensory-evoked all-or-none cortical population responses were observed in the mouse auditory cortex in vivo and similar stochastic cortical responses were observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…This reduction was due to short-term synaptic depression of the TRN-thalamus synapse, with a minimal contribution from the intrinsically mediated reductions in TRN spiking (the intrinsic burst properties of TRN neurons cannot follow high frequencies; Crandall et al, 2015 ). A recent study in the auditory system investigated the mechanisms underlying the gating of all-or-none population responses in the auditory cortex via L6 CT-TRN feedback (Ibrahim et al, 2021 ). They present an alternative mechanism by which the gating of cortical activity mediated by L6 CT-TRN feedback is dependent on the ability of the TRN to desynchronize thalamocortical neurons rather than diminishing thalamic activity (Ibrahim et al, 2021 ).…”
Section: L5 and L6 Corticothalamic Projections Provide Different Inputs To Thalamic Neuronsmentioning
confidence: 99%
See 3 more Smart Citations
“…This reduction was due to short-term synaptic depression of the TRN-thalamus synapse, with a minimal contribution from the intrinsically mediated reductions in TRN spiking (the intrinsic burst properties of TRN neurons cannot follow high frequencies; Crandall et al, 2015 ). A recent study in the auditory system investigated the mechanisms underlying the gating of all-or-none population responses in the auditory cortex via L6 CT-TRN feedback (Ibrahim et al, 2021 ). They present an alternative mechanism by which the gating of cortical activity mediated by L6 CT-TRN feedback is dependent on the ability of the TRN to desynchronize thalamocortical neurons rather than diminishing thalamic activity (Ibrahim et al, 2021 ).…”
Section: L5 and L6 Corticothalamic Projections Provide Different Inputs To Thalamic Neuronsmentioning
confidence: 99%
“…A recent study in the auditory system investigated the mechanisms underlying the gating of all-or-none population responses in the auditory cortex via L6 CT-TRN feedback (Ibrahim et al, 2021 ). They present an alternative mechanism by which the gating of cortical activity mediated by L6 CT-TRN feedback is dependent on the ability of the TRN to desynchronize thalamocortical neurons rather than diminishing thalamic activity (Ibrahim et al, 2021 ). They suggest that thalamic synchronization by the TRN can be a mechanism to recruit neuronal populations for sensory representations (Ibrahim et al, 2021 ).…”
Section: L5 and L6 Corticothalamic Projections Provide Different Inputs To Thalamic Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…As anatomical and physiological studies have shown (see section “A1-MGBv Corticothalamic Pathway”; Guo et al, 2017 ), corticothalamic feedback modulates not only MGBv but also A1 and TRN. Furthermore, corticothalamic feedback via TRN inhibiting MGBv seems to determine whether A1 neurons respond to weak tones or not ( Ibrahim et al, 2021 ). Future investigations will need to explore the joint effects of the combined thalamocortical-corticothalamic-corticoreticular-intracortical loop.…”
Section: Cortical Manipulation Onto Mgbv Neuronsmentioning
confidence: 99%